Evaluation of the Mean Duration of Recent Infection (MDRI) and the False Recent Rate (FRR) for the Limiting Antigen Avidity Enzyme Immune Assay (LAg) and Bio-Rad HIV ½ Plus O Avidity Incidence Assay (BRAI) - Gonese, Elizabeth (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhD)--Stellenbosch University, 2017.